PENGARUH PEMBERDAYAAN USAHA KECIL DAN MENENGAH (UKM) TERHADAP PENGEMBANGAN EKONOMI LOKAL DI KOTA MEDAN - ANTON ATNO PARLUHUTAN SINAGA (JURNAL ILMIAH KOHESI, 2020)
People empowerment is the basic element which enables a community to survive, and in a dynamic term it means todevelop one’s self and to achieve progress. UKM (Small and Medium Enterprise) empowerment constitutes a treatmentwhich is given to powerless UKM in order to make it powerful; in this case, it will eliminate or at least reduce itspowerlessness and actualizes its potency and utilizes its opportunity. The objective of the research was to find out somefactors which influenced UKM empowerment and people’s welfare in Medan. The research used descriptive quantitativemethod, and the data were gathered by using secondary and primary data, and the hypothesis was tested by using datasamples. Structural Equation Modeling (SEM) was used as Statistical Inferential method in analyzing the data. The result ofthe research showed that, first, institutional empowerment, local enterprise authority empowerment, stakeholdersempowerment, space empowerment, increase in access to financing sources, empowerment in production through the aid ofselective business sector as stimulant, marketing network development, human resources empowerment, information andtechnology empowerment, and monitoring and evaluation empowerment were ten factors which had positive and significantinfluence on UKM empowerment in Medan; secondly, life quality from material viewpoint, life quality from physical viewpoint,life quality from mental viewpoint, and life quality from spiritual viewpoint were four factors which had positive and significantinfluence on people’s welfare in Medan; and three, UKM empowerment had negative but significant influence on people’swelfare in Medan.